The value of tropical forest to local communities: complications, caveats, and cautions - Sheil, Douglas; Wunder, Sven (2002)
The methods used to value tropical forests have the potential to influence how policy makers and others perceive forest landsforestlands. A small number of valuation studies achieve real impact. These are generally succinct accounts supporting a specific perception. However, such reports risk being used to justify inappropriate actions. The end users of such results are rarely those who produced them and misunderstanding of key details is a concern. One defence is to ensure that the ultimate users appreciate shortcomings and common pitfalls. In this article, the authors aim to reduce such risks by discussing how valuation studies should be assessed and challenged by users. The authors consider two concise, high profile valuation papers here, by Peters and colleagues and by Godoy and colleagues. They illustrate a series of questions that should be asked, not only about the two papers, but also about any landscape valuation study. The article highlighted the many challenges faced in valuing tropical forest landsforestlands and in presenting and using results sensibly, and it offers some suggestions for improvement. Attention to compexitiescomplexities and clarity about uncertainties are required. Forest valuation must be pursued and promoted with caution.